Pre-service language teacher wellbeing as a complex dynamic system. (December 2021) - Sulis, Giulia; Mercer, Sarah; Mairitsch, Astrid; Babic, Sonja; Shin, Sun
Abstract: Pre-service teachers face a number of challenges which might threaten their wellbeing, including negotiating their student and teacher roles, and difficulties in managing their pupils and workload (Day & Gu, 2010). Due to the Covid-19 pandemic, they have been confronted with additional challenges resulting from the transition to online learning and teaching, as well as social problems caused by lockdowns. In this study, we explore the wellbeing of six pre-service language teachers through individual interviews conducted during the first wave of the pandemic. The study has two main aims. Firstly, we seek to identify how these pre-service teachers coped with the challenges of becoming a teacher in the context of a major disruption to their wellbeing. Secondly, we aim to contribute to theoretical work in this field by examining their wellbeing from a Complex Dynamic Systems Theory (Larsen-Freeman & Cameron, 2008) perspective to explore the dynamic and complex nature of the construct. Findings revealed that the pandemic served as a critical incident leading to diverse attractor states for each individual's wellbeing. They also show how agency played a key role in guiding the trajectory of the teachers' wellbeing system, and that this was contingent upon individual perceptions of environmental affordances.